THE EFFECT OF RICE CULTIVARS ON METHANE EMISSION FROM IRRIGATED RICE FIELD - Setyanto, P.; Rosenani, A.B.; Boer, R.; Fauziah, C.I.; Khanif, M.J. (Indonesian Agency for Agricultural Research and Development - MOA, 2004)
Rice plants have been reported to affect methane (CH4) emission from rice fields. The objectives of this study were to determine the effect of rice cultivars on CH4 emission from flooded rice and to develop crop management strategies with low emitting rice cultivars while sustaining high yield. The four rice cultivars studied were Memberamo, Cisadane, IR64, and Way Apoburu. The CH4 emissions were determined in the wetseason of 2001/2002 (November-February) using an automated closed chamber technique in an irrigated field condition. Farmyard manure at the rate of 5 t ha-1 was given to the plots to ensure carbon was not limited. Root weight, root length, biomass, and number of tillers were determined at 17, 36, and 57 days after transplanting (DAT). The results showed that the mean CH4 emission was highest in the plot planted with Cisadane (94.8 kg CH4 ha-1), and the lowest with IR64 (37.7 kg CH4 ha-1). The plots treated with Memberamo and Way Apoburu resulted an intermediate CH4 emission at the average of 61.1 and 58.9 kg CH4 ha-1, respectively. There was no significant difference in yield between the cultivars tested. The yield of Memberamo, Cisadane, IR64, and Way Apoburu were 5.882, 5.764, 5.873 and 6.065 t ha-1, respectively. Statistical analysis showed that there were no significant differences in the root weight and root length among cultivars. However, Cisadane gave the highest dry matter weight (222 g hill-1) at 57 DAT compared to the other cultivars (175-190 g hill-1). Plant tillers did not show significant differences between the cultivars. Regression analysis showed that CH4 flux was significantly related with root weight, root length, aboveground biomass, and number of plant tillers. This finding shows that the use of selected cultivars, such as IR64, can potentially lower CH4 emission without scarifying yield.